The Analysis of Market Orientation and Entrepreneurship Orientation on Company Performance Based on the Supply Chain Strategy - Aidin Shakouri; Arash Mohammad Zadeh Shakouri (International Journal of Supply Chain Management, 2020)
Abstract- The goal of present paper is testing the entrepreneurship marketing model for analysis the effects of marketing strategies, entrepreneurship orientation, marketing orientation and performance of companies in Jey industrial park based on the supply chain strategy. For this goal we present seven hypotheses. In order to gathering necessary information for testing these hypotheses, we were used an author constructed questionnaire, this questionnaire consists of 34 questions in 6 dimensions and were distributed between 110 managers in Jey industrial park.  For analysis of data and the results of hypotheses, we use structural equation modeling in the way of Partial Least Square or PLS and using the Smart Pls software. The results show that between all discussed variable, except entrepreneurship orientation, there is a positive and meaningful effect with the marketing entrepreneurship. In addition, between all discussed variable there is a positive and meaningful effect with the company performance.